2017
DOI: 10.1016/s2214-109x(17)30392-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification and management of Shigella infection in children with diarrhoea: a systematic review and meta-analysis

Abstract: SummaryBackgroundShigella infections are a leading cause of diarrhoeal death among children in low-income and middle-income countries. WHO guidelines reserve antibiotics for treating children with dysentery. Reliance on dysentery for identification and management of Shigella infection might miss an opportunity to reduce Shigella-associated morbidity and mortality. We aimed to systematically review and evaluate Shigella-associated and dysentery-associated mortality, the diagnostic value of dysentery for the ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
76
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(84 citation statements)
references
References 52 publications
3
76
0
5
Order By: Relevance
“…Our findings of sex and age distribution showed that: 1) male individuals were more likely to be infected by Shigella spp than females; 2) individuals who were infants or old were more likely to be infected by the pathogen. These findings are similar to the epidemiological characteristics of shigellosis [24,32,33]. The intervention focusing on male, children, newborns and elders might be more effective to prevent and control the disease.…”
Section: The Epidemiological Characteristics Of the Diseasesupporting
confidence: 80%
“…Our findings of sex and age distribution showed that: 1) male individuals were more likely to be infected by Shigella spp than females; 2) individuals who were infants or old were more likely to be infected by the pathogen. These findings are similar to the epidemiological characteristics of shigellosis [24,32,33]. The intervention focusing on male, children, newborns and elders might be more effective to prevent and control the disease.…”
Section: The Epidemiological Characteristics Of the Diseasesupporting
confidence: 80%
“…A systematic review on chikungunya virus infection-related rheumatic and musculoskeletal disorders identified chloroquine, hydroxychloroquine, disease-modifying antirheumatic drugs, corticosteroids, and nonsteroidal anti-inflammatory drugs as therapeutic options, but also highlights the lack of high-quality data to guide treatment decisions. 23 Tickell et al 28 performed a systematic review of Shigella infection in children. Dysenteric Shigella infections are often clinically obvious and are treated with antibiotics, but Shigella infections without symptoms of dysentery can be very difficult to detect.…”
Section: Discussionmentioning
confidence: 99%
“…Infection by Shigella is a leading cause of diarrhoea in children in low‐ and middle‐income countries, where it is associated with high mortality rates (Tickell et al, ). There are four Shigella species, two of which ( S. flexneri and S. sonnei ) cause 90% of all infections.…”
Section: Shigella – Inflammasome Interactions Are Cell‐type Specificmentioning
confidence: 99%
“…Infection by Shigella is a leading cause of diarrhoea in children in lowand middle-income countries, where it is associated with high mortality rates (Tickell et al, 2017). Compared to studies with Salmonella, much less is currently known about the roles inflammasomes play during Shigella infection.…”
Section: Shigella -Inflammasome Interactions Are Cell-type Specificmentioning
confidence: 99%